SOUND EMOTION MAPPING USING DEEP LEARNING - Chaudhari, Dr. Sachin Vasant; Sargam, Sadhana; Kandhari, Harsimrat; Taneja, Madhur; Panda, Sourav; L.Sujihelen, (ShodhKosh: Journal of Visual and Performing Arts, 2025)
Emotion recognition from sound is an important area of affective computing where machines can use vocal cues as an indication of human emotions for empathic and adaptive interactions. Traditional methods based on handcrafted acoustic features like MFCCs and LPC are restricted in terms of nonlinear and context-dependent emotional dynamics and mostly suffer from speaker and recording condition variations. To solve these issues, in this study the deep learning-based sound emotion mapping framework based on the combination of Convolutional Neural Networks (CNNs) for the spatial feature extraction and Long Short-Term Memory (LSTMs) for the temporal modeling has been proposed. CNN layers detect spectrogram patterns of the log-mel spectrograms and prosodic cues whereas LSTMs detect the transitions in emotions sequentially resulting in a powerful end-to-end system which does not require manual feature design. Using RAVDESS and Berlin EMO-DB testing datasets, the proposed CNN-LSTM model obtained an accuracy of 93.2% and 91.4% respectively over performing SVM and CNN-only baselines. Attention-weight visualization showed that the model attention is concentrated on the mid-frequency region, which is in line with the psychoacoustic theories of emotional prosody.